Nash-Cournot or Lindahl Behavior?: An Empirical Test for the Nato Allies - Sandler, Todd; Murdoch, James C. (Quarterly Journal of Economics, 1990)
This paper derives systems of demand equations for distinguishing between Nash-Cournot and Lindahl behavior in a group that either shares a pure public good or an activity that provides a private and a pure public joint product. Systems of simultaneous equations are estimated based upon Nash-Cournot and Lindahl behavior for a sample of ten NATO allies for the 1956–1987 period. Nonnested hypothesis tests support the Nash-Cournot specification for five of the ten sample allies. No evidence of Lindahl behavior is found. The Nash-Cournot joint-product specification outperforms the pure public model for all sample allies.